A new species of Hetereleotris (Perciformes: Gobiidae) from Farasan Island (Red Sea) - Kovačić, Marcelo; Bogorodsky, Sergey V.; Mal, Ahmad O. (Zootaxa, 2014)
A new species of the genus Hetereleotris is described from Farasan Island, Saudi Arabia, Red Sea, on the basis of a single specimen. Hetereleotris dorsovittata sp. nov is unique among the known sixteen species of Hetereleotris, except for H. diademata and H. psammophila, in the combination of the absence of head canals and lack of squamation. The low count of pectoral-fin rays (14) is only overlap with H. psammophila (14 or 15), whereas all other Hetereleotris species have a higher number of pectoral-fin rays. The new species differs from H. psammophila in having more soft rays in the dorsal and anal fins, by the arrangement of papillae in the preoperculo-mandibular row i and by coloration. The single specimen was collected in the large lagoon at the base of an isolated small coral patch at a depth of 1m.